An introduction to qualitative research - Flick, Uwe, 1956- (Los Angeles : SAGE, 2023)
This book looks at both the theory behind qualitative research and how to put it into practice in your own work. For students across a range of social science disciplines and beyond, this book will help you enhance your research project.
Previous edition of this translation: 2018.
Translated from the German.
Includes bibliographical references (pages 556-585) and index.
Keywords: Qualitative research; Social sciences -- Research -- Methodology; Psychology -- Methodology -- Handbooks, manuals, etc; Social sciences -- Methodology -- Handbooks, manuals, etc; Qualitative research -- Handbooks, manuals, etc; Qualitative research -- Case studies; Qualitative research -- Problems, exercises, etc; social sciences; Psychology -- Methodology; Qualitative research; Social sciences -- Methodology; Social sciences -- Research -- Methodology